Analysis Of The Economic Capacity Of Tourism Destinations On The South Coast Of East Java - Imam Sukwatus Suja’i (International Conference On Law And Social Sciences, 2024)
This study aims to analyze the economic capacity of tourism destinations on the south coast of East Java. Using a mixed-method approach, this research combines quantitative and qualitative analyses to assess economic potential, environmental carrying capacity, and stakeholder perceptions. The results indicate that tourism destinations on the south coast of East Java have significant economic potential but still face challenges in terms of infrastructure, environmental management, and inter-stakeholder coordination. This study provides recommendations for developing sustainable economic capacity of tourism destinations.